Efektivitas Permainan Puzzle Tangkai Es Kereta Api terhadap Kemampuan Membaca di Taman Kanak-Kanak Yayasan Wanita Kereta Api Padang - Daniati, Riski; Jaya, Indra; Yeni, Indra (JFACE: Journal of Family, Adult, and Early Childhood Education, 2019)
The purpose of this study is to know the effectiveness of the Train Ice Stalk Puzzle Game againts Reading Ability in Taman Kanak-kanak Yayasan Wanita Kereta Api Padang. This type of researchis quantitative methods to research the type of experiment or quasy experiment (experiment pseudo) by using ihe Train Ice Stalk Puzzle Game. The Train Ice Stalk Puzzle Game take effective in Taman Kanak-kanak Yayasan Wanita Kereta Api Padang. Based on data analysis, the average values obtained results the skill of children reading in the experiment class that uses Train Ice Stalk Puzzle Game higher (84,5) than the control class that uses Sterofoam Puzzle game (69).